PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN UPAH TERHADAP PRODUKTIVITAS KERJA (Studi Kasus pada Karyawan Bagian Produksi Perum Perhutani Industri Kayu Brumbung) - Santosa, Satria Teguh; Hidayat, Wahyu; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Increased labor productivity is a key factor for the development of a company in order to progress. Definition of productivity itself is a total output resulting from the use of a certain quantity of labor, or the quantity of total output compared with the quantity of labor. One important factor that must be considered firms in an effort to increase the productivity of labor is comfort working environment. Comfortable working environment will be able to generate enthusiasm and excitement employee. Motivational support, a good working environment and conducive and fun will encourage employees to work well too and also recompense in the form of wages more than sufficient to be one of the critical success factors of labor productivity. Therefore, three things need to be considered in improving employee productivity by Perum Perhutani Wood Industry Brumbung. Work environment, motivation and reward have an influence either directly or indirectly in increasing the productivity of labor.This type of research is Explanatory Research. The research sample of 110 respondents. Samples were taken using a non-probability sampling techniques or methods census. Data were analyzed qualitatively and quantitatively using a data collection instrument (questionnaire) was previously tested through validity and reliability test. While the results of the data analysis is done through the analysis of tables, simple linear regression analysis, multiple linear regression analysis, t test, F test with SPSS.The results showed that the work environment , motivation and reward both partially and simultaneously significant effect on work productivity . Based on the calculation of data analysis through a simple regression test concluded that the work environment affect the productivity of labor, work motivation effect on work productivity, and wages influence the work productivity as well as through multiple regression test concluded that the work environment, motivation and reward effect on work productivity shows significant results.